2017
DOI: 10.5628/rpcd.17.s4a.115
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência do uso de esteroides anabólicos androgênicos em praticantes de musculação de Teresina-PI

Abstract: Obesity, insulin resistance, diabetes, and cardiovascular risk in children an american heart association scientific statement from the atherosclerosis, hypertension, and obesity in the young committee (council on cardiovascular disease in the young) and the diabetes committee (council on nutrition, physical activity, and metabolism).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
2
1
Order By: Relevance
“…Regarding education levels of the subjects, our results differ from previous studies [98], in which most subjects had completed high school, followed by higher education in progress. Our study showed that some of the subjects had completed higher education.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding education levels of the subjects, our results differ from previous studies [98], in which most subjects had completed high school, followed by higher education in progress. Our study showed that some of the subjects had completed higher education.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, other studies presented a prevalence close to 5.7% [28] and 7% [14]. However, some studies did not report the use of AS by women [15, 23, 29]. AS consumption is lower among women because they do not wish to become extremely muscular or develop male characteristics [30].…”
Section: Discussionmentioning
confidence: 99%
“…There was a higher percentage of individuals with incomplete upper and lower secondary education among future users of AS, corresponding to individuals aged between 18 and 29 years, which showed the highest frequency of future users of AS. This finding emphasized the need for orientation regarding the use of AS in schools and universities, considering that AS use was also high in individuals with incomplete upper secondary education [29].…”
Section: Discussionmentioning
confidence: 99%